(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English Urban growth in developing countries show an undesired symtoms. To anticipate the backwardness, urban areas have been driven strongly to increase demand of goods and services for all over national interest. As result, the existing urban is not only matter of spatial as well as economic structural changes, but also performing social and environmental implications. It can be seen in Bogota with an dualism pattern of its social system, the existence of the spatial separation between rich people in the northern and the poor in south and west. The similar phenomenon have been also found in Indonesia. Jakarta have developed very quickly supported by increasing in manufacture and finance sectors, yielding an outstanding economic gains and revenues for the people. However, beyond these conditions there are an unavoidable significant cost that commonly appear as environment quality deterioration. Recommended policies are (1) To improve urban economic productivity which integrated into regional and rural development (2) To increase productivity of urban poor people through improvement of social infrastructure and widening employment, (3) To avoid environment degradation as well as others consequences around poor people areas, and (4) To build an equal perception about urban development and related problems among stakeholders: government, private sectors, and people. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Pertumbuhan daerah kota di negra berkembang menunjukan gejala yang tidak di harapkan.untuk mengantisipasi kondisi keterbelakangan ini, daerah perkotaan haurus di dorong secara kuat untuk meningkatkan permintaan terhadap barang dan pelayanan untuk seluruh kepentingan nasional. permasalahan kota yang telah di hadapi bukan hanya persoalan keruangan dan perubahan struktur ekonomi saja, tapi juga pembentukan implikasi sosial dan lingkungan. hal ini dapat di lihat di Bogota dengan pola dualisme sistem sosialnya, adanya pemisahan ruang antara masyarakat kaya di daerah utara dan masyarakat miskin di daerah selatan dan barat. Fenomena serupa juga di temukan di Indonesia. Jakarta yang berkembang secara cepat dengan dukungan sektor manufaktur dan keuanga, mencapai kondisi ekonomi dan pendapatan yang baik. Bagaimanapun, di balik kondisi tersebut, ditemukan biaya yang tak terhindarkan secara nyata, yang umum muncul berupa penurunan kualitas lingkungan. Beberapa kebijaksanaan direkomendasikan adalah: (1) Meningkatkan produktivitas ekonomi wilayah kota yang terintegrasi ke dalam pembangunan regional dan pedesaan, (2) Meningkatkan produktivitas kelompok miskin perkotaan melalui perbaikan infrastruktur sosial dan perluasan kesempatan kerja, (3) Menghindari perusakan lingkungan serta konsekwensi lainnya di sekitar wilayah masyarakat miskin, dan (4) Membangun persepsi yang seimbang terhadap pembangunan kota dan permasalahan-permasalahan yang berkaitan dengannya: pemerintah, sektor swasta, dan masyarakat.